Treatment methods of paresthesia of the inferior alveolar nerve after surgery - Z. S. Khabadze; A. V. Zoryan; K. N. kizi Kerimova; O. I. Magomedov; Sh. A. Nazhmudinov; M. G. Abdullaev (LLC "Endo Press", 2020)
Relevance. Today, many practitioners encounter paresthesia of the inferior alveolar nerve after surgical procedures. This literature review was aimed at finding possible treatment options for paresthesia and identifying their effectiveness.